Effect of a turmeric–tamarind drink on menstrual pain intensity among adolescent girls - Marchella Audina; Eures Pinka (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Dysmenorrhea is one of the most common gynecological problems experienced by adolescent girls during menstruation. Menstrual pain can disrupt daily activities, concentration, academic performance, and quality of life. Non-pharmacological therapies have been widely used to reduce menstrual pain, one of which is tamarind and turmeric therapy. Tamarind and turmeric contain curcumin and anthocyanins, which have anti-inflammatory, analgesic, and antispasmodic properties, which can help reduce prostaglandin production and uterine contractions. Purpose: To determine and analyze the effect of tamarind and turmeric therapy on reducing menstrual pain intensity in adolescent girls. Method: This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 40 adolescent girls experiencing dysmenorrhea and were selected using purposive sampling. Pain intensity was measured using a Numeric Rating Scale (NRS). Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Results: Before the intervention, most respondents experienced moderate to severe menstrual pain with an average pain score of 6.35. After receiving tamarind and turmeric therapy, the average pain score decreased to 2.95. The Wilcoxon Signed Rank Test showed a significance value of p = 0.000 (p < 0.05), indicating a statistically significant reduction in menstrual pain intensity after the intervention. Conclusion: Tamarind and turmeric therapy significantly reduced menstrual pain intensity in adolescent girls.